EXPERIMENTAL MODEL OF FUTURE HISTORY TEACHERS' TRAINING FOR ETHNOCULTURAL ACTIVITY IN SOUTHERN UKRAINE - Юлія Бєгунова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article is devoted to the problem of History teachers' training in terms of multicultural environment of Southern Ukraine. The author develops a model of the given process and characterizes its structural units. It has been shown, that in ethnographic context multinationality is a peculiarity of this region. The researcher grounds, that a future History teacher in Southern Ukraine has to be ready to work in such a multi-ethnic, multicultural and multi-faith society. It required definition of the pedagogical conditions for to realization of possibilities of ethnocultural experience in the process of future History teachers' training. According to the purpose of research, the article provides scientific grounds for each pedagogical condition. The author proves, that consideration of interaction of the specified conditions provides productive ethnocultural activity of future History teachers in Southern Ukraine.